(untitled) (Agroindustrial Science, 2024)
The purpose of this research work was to know the contamination of the soil of papaya crops (Carica papaya), by the application of agrochemicals in the control of pests and diseases. Where soil samples were taken from 5 papaya plots (Carica papaya), 15 samples of 1 kg each of soil were extracted, followed by a plot without anthropic intervention of 3 samples to be sent to the laboratory. From the results, the agrochemicals used in papaya (Carica papaya) crops were determined, such as fire herbicides, propanil, hedonal and glyphosate; as insecticides dimethoate and aldrin; as fungicides zineb, mancozeb WP and Champion. It was found that cadmium had the highest concentration of 1.677 mg/kg, followed by lead at 13.297 mg/kg and chromium VI with its maximum concentration of 0.7833 mg/kg. The alternatives as strategies for the use of agrochemicals were catahua resin (Hura crepitans) that acts as a pesticide, cocoa honey water herbicides, solid organic fertilizers (solid chicken manure fertilizer, cattle manure compost, vermicomport, compost of pulp of coffee) and barbasco bark (Lonchpocarpus nicou). It was concluded that the soils of papaya (Carica papaya) crops are contaminated by the excessive use of agrochemicals in the control of pests, diseases, and improvement of production.